Chaihu-shugan-san alleviates depression-like behavior in mice exposed to chronic unpredictable stress by altering the gut microbiota and levels of the bile acids hyocholic acid and 7-ketoDCA - Ma, Chong; Yuan, Dun; Renaud, Stephen James; Zhou, Ting; Yang, Fan; Liou, Yuligh; Qiu, Xinjian; Zhou, Lu; Guo, Ying (Frontiers in Pharmacology, 2022)
Chaihu-Shugan-San (CSS) is a traditional botanical drug formula often prescribed to treat depression in oriental countries, but its pharmacotherapeutic mechanism remains unknown. It was recently reported that CSS alters the composition of intestinal microflora and related metabolites such as bile acids (BAs). Since the intestinal microflora affects physiological functions of the brain through the gut-microbiota-brain axis, herein we investigated whether CSS altered BA levels, gut microflora, and depression-like symptoms in chronic unpredictable mild stress (CUMS) mice, a well-established mouse model of depression. Furthermore, we determined whether BA manipulation and fecal microbiota transplantation altered CSS antidepressant actions. We found that the BA chelator cholestyramine impaired the antidepressant effects of CSS, which was partially rescued by dietary cholic acid. CSS increased the relative abundance of Parabacteriodes distasonis in the colon of CUMS mice, and increased serum levels of various BAs including hyocholic acid (HCA) and 7-ketodeoxycholic acid (7-ketoDCA). Furthermore, gut bacteria transplantation from CSS-treated mice into untreated or cholestyramine-treated CUMS mice restored serum levels of HCA and 7-ketoDCA, alleviating depression-like symptoms. In the hippocampus, CSS-treated mice had decreased expression of genes associated with BA transport (Bsep and Fxr) and increased expression of brain-derived neurotrophic factor and its receptor, TrkB. Overall, CSS increases intestinal Parabacteriodes distasonis abundance, leading to elevated levels of secondary BAs in the circulation and altered expression of hippocampal genes implicated in BA transport and neurotrophic signaling. Our data strongly suggest that the gut microbiota-brain axis contributes to the potent antidepressant action of CSS by modulating BA metabolism.